Koncept prediktivnog održavanja 4.0 (PdM) u energetici – konekcija sa budućom primenom Industrije 5.0 - Jovančić, Predrag; Ignjatović, Dragan; Đenadić, Stevan; Tanasijević, Miloš; Miletić, Filip (Energija, ekonomija, ekologija : list Saveza energetičara, 2022)
Industry 4.0 marks the fourth industrial revolution, characterized by the use of cyber-physical systems. In order to achieve an optimal maintenance strategy (but also production), it is necessary to develop systems that support advanced intelligent maintenance systems or smart maintenance technologies. This resulted in the postulates of Predictive Maintenance 4.0, which define the very near future in the field of maintenance of technical systems. Predictive Maintenance 4.0 involves harnessing the power of artificial intelligence to create ongoing insights into detecting causes and anomalies in equipment operations that are not detected by cognitive power. In other words, Predictive Maintenance 4.0 makes it possible to predict what was previously unpredictable. Industry 5.0 focuses on the return of human hands and minds to the industrial framework. The man and machine harmonize with each other and find ways to work together to improve production / maintenance efficiency.